ANALISIS KESALAHAN MORFOSINTAKSIS TEKS CERITA FANTASI KARYA PESERTA DIDIK KELAS VII UPTD SMP NEGERI 1 PAREPARE - Tamsiruddin (Universitas Hasanuddin, 2023)
This study aims to describe the morphosyntactic errors of fantasy story texts by students of class VII UPTD SMP Negeri 1 Parepare. The research method used in this research is a qualitative method with a descriptive analysis research design. This study presents data in the form of a description of the morphosyntactic construction errors found in fantasy story texts by students of class VII.1 UPTD SMP Negeri 1 Parepare. The results of this study indicate that there are more morphological errors than syntax errors. The three most common errors in morphology are (1) the use of clitic -ku, -mu, -nya, (2) the use of the prefix di- and the preposition di, and (3) the writing of standard words. In the field of syntax, the errors found included (1) errors in the use of the subject in sentences, (2) the use of incomplete sentences, and (3) the use of inappropriate extensions.